PTH-120 How Can We Improve Recruitment and Support Gastroenterology Trainees in The UK? Results from The Supporting Women in Gastroenterology (SWIG) Survey. (17th August 2016) - Arthurs, E; Brooks, A; Taylor, E; Solomon, J; Neild, P; Thomas-Gibson, S; Lockett, M; Edwards, C; Eaden, J
Abstract : Introduction: In gastroenterology, whilst numbers are increasing, women remain under-represented at both trainee and consultant grade compared with other medical specialties at 52% and 34% respectively. 1 The aim of this survey was to identify the key issues around recruitment and support of trainees and consultants. Methods: A comprehensive survey was designed and circulated to consultants and trainees in gastroenterology, all of whom were members of the BSG. Data regarding demographics, working patterns, professional experiences and opinions was collected and analysed. Results: The survey was sent to 1900 people, 600 people opened the email and 186 responded, a response rate of 9.79%. 107 of respondents were female (62.9%), 16 respondents did not declare gender. Data was available for 183 responses. Important reasons for choosing a career in gastroenterology were practical procedures (23.3% of responses; n = 117, 59.8% female versus 39.3% male (gender not declared n = 1), a positive prior gastroenterology job (19.9%; n = 100, 66% female versus 34% male) and an inspirational local gastroenterologist (14.7%; n = 74; 63.5% female versus 35.1% male (gender not declared n = 1)).155 (94.5%) respondents would recommend a career in gastroenterology to a junior doctor (60% female versus 38.7% male (gender not declared n = 1)). Important factors in encouraging junior doctors to become gastroenterologists were reducing GIM activity (17.7% of responses; n = 91, 60.4% female versus 38.4% male (gender not declared n = 1)), role models (14.2%; n = 73, 68.5% female versus 31.5% male) and mentorship schemes (11.9%; n = 61, 60.7% female versus 37.7% male (gender not declared n = 1)). Factors thought to be helpful in supporting existing trainees were mentorship schemes (17.1% of responses; n = 78, 60.3% female versus 39.7% male), additional training and networking (14.5%; n = 66, 51.5% female versus 48.5% male) and reducing out of hours activity (13.1%; n = 60, 68.3% female versus 31.7% male). Conclusion: Recruitment to gastroenterology could be improved by reducing GIM activity and developing mentorship schemes. Mentorship schemes, access to additional training and networking and reducing out of hours commitments were thought to be the most useful factors that would support existing trainees. It would be beneficial to focus on developing solutions for these key issues. Reference: 1 Census of consultant physicians and higher speciality trainees in the UK, 2014-2015. Royal College of Physicians, 2016. Disclosure of Interest: None Declared